Effect of simulated air dive and decompression sickness on the plasma proteome of rats. Issue 5 (May 2016) - Lautridou, Jacky; Pichereau, Vianney; Artigaud, Sébastien; Buzzacott, Peter; Wang, Qiong; Bernay, Benoit; Driad, Sabrina; Mazur, Aleksandra; Lambrechts, Kate; Théron, Michael; Guerrero, François
Abstract : Purpose: Decompression sickness (DCS) is a poorly understood systemic disease caused by inadequate desaturation following a reduction in ambient pressure. Although recent studies highlight the importance of circulating factors, the available data are still puzzling. In this study, we aimed to identify proteins and biological pathways involved in the development of DCS in rats. Experimental design: Eighteen male Sprague‐Dawley rats were subjected to a same simulated air dive to 1000 kPa absolute pressure and divided into two groups: no DCS or DCS. A third control group remained at atmospheric pressure. Venous blood was collected after hyperbaric exposure and the plasma proteomes from four individuals per group were analyzed by using a two‐dimensional electrophoresis‐based proteomic strategy. Results: Quantitative analysis identified nine protein spots with abundances significantly changed (false discovery rate < 0.1) between the tested conditions. Three protein spots, identified as Apolipoprotein A1, Serine Protease Inhibitor A3K (Serpin A3K), and Alpha‐1‐antiproteinase, appeared increased in DCS animals but displayed only weak changes. By contrast, one protein spot identified as Transthyretin (TTR) dramatically decreased (i.e. quite disappeared) in animals displaying DCS symptoms. Before diving, TTR level was not different in DCS than nondiving group. Conclusion: These results may lead to the use of TTR as an early biomarker of DCS.